A Passive Vision System for Weld Bead Inspection System Textures in Underwater Environments - Baldez, Patrick; Soares, Luciane; Debiaze, Débora; Botelho, Silvia; Nagel, Ricardo; Espíndola, Danubia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
Since approximately 1960, remote operating vehicles (ROVs) have been in use, but they have performed a limited number of tasks. Over the years and with technological advances, the ROVs have been gaining new tools and possibilities that have provided a new range of applications, including the inspection of structures in underwater environments. In the oil and gas sector, for example, it is essential that there is efficiency, care and safety with workers, as well as with production places and instruments. In this way, visual inspection techniques and underwater non-destructive tests are important in determining the quality of the operation. Oil platforms and ships are built with welded steel plates. With the action of time and sea water they start to suffer degradations. Visual inspection of steel welds in an underwater environment is essential, because the existence of discontinuities, geometric imperfections or faults can impair the safety of the structures. Thus, the main contribution of this work is to present a method capable of identifying irregularities in the texture of the weld bead of sheet metal used for heavy steel structures, in underwater environments.